The conquered - Thayer, Kristen Marie, author; Levy, E. J., advisor; Becker, Leslee, committee member; Khrebtan-Hörhager, Julia, committee member (Colorado State University. Libraries, 2014)
The Conquered is a novel about the unintended consequences that spiral out of deeply felt emotions and unresolved conflicts--about how the little things, unchecked, become the big things. It is about the cycles of good and evil that are experienced and passed on, both intentionally and unintentionally, and the small acts of understanding that make us human. This is a novel primarily about women: their concerns, their choices, their public and private griefs. It is an epic tale of mothers and daughters, of communities linked by faith and torn apart by prejudices. Set among the Uyghurs of northwestern China, a Muslim minority totaling ten million people, The Conquered follows the lives of three Uyghur women--Habiba, an ambitious middle-aged shopkeeper whose success in the world of business puts her personal and familial relationships in jeopardy; Zulpiya, the shopkeeper's teenaged daughter who is caught between the Han and Uyghur worlds because of her success in the Han educational system; and Rashida, a young woman attending Xinjiang University who gets involved with the growing Uyghur separatist movement. The narration spans the period from April 2008 (just before the 2008 Beijing Olympics) to August 2009 (just after the July 2009 ethnic riots in Urumqi).